Dynamic charge order from strong correlations in the cuprates - da Silva Neto, Eduardo H.; Frano, Alex; Boschini, Fabio (Frontiers in Electronic Materials, 2024)
Charge order has been a central focus in the study of cuprate high-temperature superconductors due to its intriguing yet not fully understood connection to superconductivity. Recent advances in resonant inelastic x-ray scattering (RIXS) in the soft x-ray regime have enabled the first momentum-resolved studies of dynamic charge order correlations in the cuprates. This progress has opened a window for a more nuanced investigation into the mechanisms behind the formation of charge order (CO) correlations. This review provides an overview of RIXS-based measurements of dynamic CO correlations in various cuprate materials. It specifically focuses on electron-doped cuprates and Bi-based hole-doped cuprates, where the CO-related RIXS signals may reveal signatures of the effective Coulomb interactions. This aims to explore a connection between two central phenomena in the cuprates: strong Coulomb correlations and CO-forming tendencies. Finally, we discuss current open questions and potential directions for future RIXS studies as the technique continues to improve and mature, along with other probes of dynamic correlations that would provide a more comprehensive picture.